Research on Seepage Properties and Pore Structure of the Roof and Floor Strata in Confined Water-Rich Coal Seams: Taking the Xiaojihan Coal Mine as an Example - Hailong Li (Advances in Civil Engineering)
During the construction and exploitation process in the Xiaojihan coal mine, which is located in Yulin of northern Shaanxi, we find a special hydrogeological phenomenon that coal seam is acted as a confined fractured aquifer. The water-rich coal seam has natural fissures which are confined with water storage. However, the water comes from the static and original reserves in coal seams, which have a weak link to other aquifers in the roof and floor strata. It indicates that the roof and floor strata provide a natural waterproof barrier for the fissure water in the coal seam, resulting in a relatively closed storage space of confined water. In order to further investigate the critical function that mechanical properties of permeability play in the confined fractured aquifer, the rock complete stress-strain permeability test and pore development structure test are carried out with rock samples of the roof and floor strata in this field. Results are as follows: (1) coal seams of Xiaojihan coal mine are confined fractured aquifers, the fissure confined water in coal seams has a strong relationship with total stress-strain permeability and development characteristics of the pore structure of the roof and floor strata. (2) The permeability of the roof and floor strata is extremely low, when the strata is less than 30 meters away from the coal seam with the magnitude order remaining less than 10−12 m/s. If they are closer to the coal seam, the watertightness and plasticity of the strata will be stronger, and the antidestructive capability of the strata during the distortion process will be also increased, resulting in the larger strain for the formation of macroscopic water-conducting fissures. The roof and floor strata effectively cut off the hydraulic connection between the fissure water in the coal seam and other aquifers, which ensure the coal seam acts as water storage space of confined fractured aquifers. (3) For undeveloped fissures, the effective porosity is less than 2% of the roof and floor strata which are less than 30 meters away from the coal seam, and particularly, this index is less than 1% of the strata within 20 meters away from the coal seam, indicating that the strata have good water resistance. When the distance between the roof strata and the coal seam is greater than 40 meters, the effective porosity has a large fluctuation, and the effective porosity of the partial strata is greater than 10%, reflecting that the rock strata fissure has been well developed. It should be attached great importance to prevent water-conducting fissures from getting hydraulic connection with the fractured water-rich coal seams and other aquifers of the roof and floor, so as to reduce the risk of mining water hazards.